2009
DOI: 10.1071/wr06066
|View full text |Cite
|
Sign up to set email alerts
|

Migration of feral pigs (Sus scrofa) in rainforests of north Queensland: fact or fiction?

Abstract: The Wet Tropics bioregion of north Queensland has been identified as an area of global significance. The worldheritage-listed rainforests have been invaded by feral pigs (Sus scrofa) that are perceived to cause substantial environmental damage. A community perception exists of an annual altitudinal migration of the feral-pig population. The present study describes the movements of 29 feral pigs in relation to altitudinal migration (highland, transitional and lowland areas). Feral pigs were sedentary and stayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 23 publications
9
43
0
Order By: Relevance
“…A number of home range analyses have found that feral pigs are relatively sedentary for their size and occupy well-defined home ranges. There were consistent gender-specific and seasonal differences in home range movements (Caley 1997;Dexter 1999;Mitchell et al 2009). Dexter (1999) found that female home ranges decreased significantly under drought conditions.…”
Section: Resource Selection and Home Range Movementsmentioning
confidence: 99%
See 4 more Smart Citations
“…A number of home range analyses have found that feral pigs are relatively sedentary for their size and occupy well-defined home ranges. There were consistent gender-specific and seasonal differences in home range movements (Caley 1997;Dexter 1999;Mitchell et al 2009). Dexter (1999) found that female home ranges decreased significantly under drought conditions.…”
Section: Resource Selection and Home Range Movementsmentioning
confidence: 99%
“…First, a large number of field studies have empirically investigated local habitat use and population densities in response to a range of environmental and biotic factors, often dynamically across seasons or years (Hone 1990a;Caley 1993Caley & 1997Corbett 1995;Choquenot 1998;Mitchell 2002;Choquenot & Ruscoe 2003;Mitchell et al 2009). For example, Caley (1993) and Hone (1990a) showed that feral pig distribution and abundance varies considerably between seasons and habitat types of varying productivity.…”
Section: Distribution and Abundancementioning
confidence: 99%
See 3 more Smart Citations